The Relationship Between Safety Climate and Safety Performance in the Large-Scale Building Construction Industry in Ethiopia: A Structural Equation Model Using the NOSACQ-50 Tool - Teferi Abegaz; Wakgari Deressa; Bente Elisabeth Moen (Safety)
A cross-sectional study of safety climate and safety performance was performed in Ethiopian construction sites, among 1203 workers from 22 large-scale construction sites. The Nordic Safety Climate Questionnaire was administered using interviews. We developed a model to show the interrelations between safety climate and performance. This model was examined using factor analysis. Low scores for all seven safety climate dimensions were found, with values ranging from 2.33 to 3.08 and a mean of 2.70. Similarly, the mean score of the safety performance construct was 2.95 for safety participation and 3.58 for safety compliance. A strong positive correlation was found between safety climate and safety performance, and safety involvement accounted for 29.2% of the variance, while safety compliance accounted for 28.6% of the variance. The suggested association between self-reported injuries and safety climate was not confirmed. Nonetheless, Pearson correlation analysis demonstrated a statistically significant negative correlation with safety climate. In conclusion, low scores for all safety climate dimensions show that safety on construction sites must be improved. The safety climate positively influences employees’ safety behavior (safety compliance and safety participation) and minimizes occupational injuries.